The Impact of The Covid-19 Pandemic on the Efficiency and Budget Performance of Vocational University in Indonesia - Muhammad Heru Akhmadi; Santorry Santorry; Aang Prabudi Sanusi (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2023)
The COVID-19 pandemic has caused a crisis in global economic growth. To confirm the situation, this research aims to determine the impact of the COVID-19 pandemic on several vocational colleges in Indonesia. This research uses a quantitative descriptive method with collected data in 2020-2021 from vocational colleges in the Directorate General of Vocational Education, Ministry of Education, Culture, Research and Technology. The results indicate a decline in budget efficiency and budget performance by 19 percent and 4.49 percent respectively. The research also proves that the college management did not anticipate the effect Covid-19 pandemic on budget efficiency and operational performance. This is identified by the absence of differences in the level of budget efficiency and performance levels at each college. This situation shows that the management did not make any efforts to maintain financial performance during the COVID-19 pandemic.